2022
DOI: 10.1038/s41598-022-07845-6
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of antibiotic resistance in pathogenic foodborne bacteria isolated from bovine milk

Abstract: This study aimed to investigate the prevalence of foodborne pathogenic bacteria in bovine milk, their antibiogram phenotype, and the carriage of antibiotic resistance genes. Raw bovine milk samples (n = 100) were randomly collected from different suppliers in the northwest of Iran. Antibiotic-resistant patterns and the presence of antibiotic resistance genes were evaluated in the isolates. Escherichia coli, Listeria monocytogenes, Staphylococcus aureus, and Salmonella spp. were isolated from 78%, 47%, 25%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…In addition, penicillin belongs to the β-lactam class of drugs, the drug has been used for long-term and repeated administration in cattle, for example, for the treatment of diarrhea and other diseases, which may result in increased resistance to its use in the treatment of clinical mastitis ( 39 ); hence, β-lactams might be the most resistant antibiotic against S. aureus . This result is supported by studies conducted in Iran ( 27 ) and Brazil ( 40 ), both showing that S. aureus is highly resistant to β-lactam antibiotics compared with other antibiotics. In India, resistance to oxacillin (a penicillin drug) can reach 20.5% ( 41 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, penicillin belongs to the β-lactam class of drugs, the drug has been used for long-term and repeated administration in cattle, for example, for the treatment of diarrhea and other diseases, which may result in increased resistance to its use in the treatment of clinical mastitis ( 39 ); hence, β-lactams might be the most resistant antibiotic against S. aureus . This result is supported by studies conducted in Iran ( 27 ) and Brazil ( 40 ), both showing that S. aureus is highly resistant to β-lactam antibiotics compared with other antibiotics. In India, resistance to oxacillin (a penicillin drug) can reach 20.5% ( 41 ).…”
Section: Discussionmentioning
confidence: 52%
“…The pooled prevalence of S. aureus in China (36.23%) is lower than that in the United States (46.6 ~ 62.4%, 118 of 189 herds) ( 21 ), Hungary (70%) ( 22 ), Northern Greece (40%) ( 23 ), and northern Ethiopia (41.7%) ( 24 ), but is higher than that in Denmark (34%) ( 25 ), Germany (7.3 ~ 11.5%) ( 26 ), Belgium (7.6%) ( 26 ), Iran (25%) ( 27 ), Japan (28.2%) ( 28 ), Nepal (15.2%) ( 29 ), and Korea (5.6%) ( 30 ). The difference in prevalence between China and the United States may be due to the fact that the scale of the United States is generally larger than that in China, and the farms covered in our study are only partial farms, and there may also be some high prevalence undetected.…”
Section: Discussionmentioning
confidence: 96%
“…Nowadays, studies on the prevalence and characterization of S. aureus isolated from final dairy products available for consumers are very common, with examples from China, Norway, and Greece, among other countries [ 24 , 25 , 26 , 27 , 28 , 29 ]. In addition, numerous articles have been published on the prevalence and characterization of S. aureus in raw milk, especially in China, Iran, and Australia [ 30 , 31 , 32 , 33 , 34 ]. It is worth emphasizing that S. aureus may enter the food chain during processing and preparation of the products [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study describes the presence of multiple AMR in foodborne bacterial isolates with biofilm formation potential, in combination with heavy metal tolerance. Previous studies have indicated that dairy products made from raw milk could be the main source of antibiotic-resistant bacteria that threaten food safety [ 21 , 36 ]. This problem is pervasive in developing countries because of poor food handling methods and hygiene standards, inadequate food safety rules and regulatory systems, and unsatisfactory education of food handlers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%